Family Interpersonal Communication Patterns in Preventing Early Marriage in Magelang Regency - Femmi Anggriyan; Prahastiwi Utari; Sudarmo (Journal of Social Interactions and Humanities, 2023)
This research aims to determine the role of communication between parents and teenagers in preventing early marriage with a focus on Magelang Regency. This research uses qualitative research methods with data collection techniques in the form of interviews, observations, and notes to examine the role of communication between parents and teenagers in preventing child marriage in Magelang Regency. The research results show that there are several types of family communication that influence the tendency to marry early. First, is democratic communication, where families can communicate openly with teenagers to provide better guidance. Second, authoritative communication, where parents are more dominant in communicating, makes teenagers feel constrained and less open. This type of authoritarian communication tends to create undisclosed problems in parents, which may contribute to early marriage among teenagers.